SOLUSI NUMERIK PERSAMAAN GELOMBANG KORTEWIEG DE VRIES (KDV) - Rumlawang, Francis Y. (PATTIMURA UNIVERSITY, 2013)
One of KdV wave form is ð‘¢ð‘¡ + 6ð‘¢ð‘¢ð‘¥ + ð‘¢ð‘¥ð‘¥ð‘¥ = 0. This paper deals with finding numerical solutions of KdVâ€™s equation which form a running wave ð‘¢(ð‘¥, ð‘¡) = ð‘¢(ð‘¥ âˆ’ ðœ†ð‘¡), by using Stepeest DescentMethod which is charged on Hamilton ð»(ð‘¢) and Momentum ð‘€(ð‘¢). By using MAPLE software, we obtain numerical solutions of KdV equation in the form of running wave profile